2022
DOI: 10.1101/2022.01.20.22269490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High prevalence of long-term olfactory disorders in healthcare workers after COVID-19: a case-control study

Abstract: Reduced olfactory function is the symptom with the highest prevalence in COVID-19 with nearly 70% of individuals with COVID-19 experiencing partial or total loss of their sense of smell at some point during the disease. Recent reports suggest that more than 7 months after recovering from COVID-19, a large proportion of these individuals still have olfactory dysfunction of some form. To establish the prevalence of olfactory dysfunction 18 months and beyond, we tested 100 individuals with established COVID-19 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 47 publications
2
17
0
3
Order By: Relevance
“…The presence of parosmia in nearly half of the smell long-haulers in our sample is not surprising for post-viral olfactory dysfunction (54) , and in other recent datasets (i.e., healthcare workers in the UK (55) and Sweden (56) , and social media scraping (18,57) , parosmia is also emerging as a common sequela of COVID-19.…”
Section: Discussionsupporting
confidence: 59%
“…The presence of parosmia in nearly half of the smell long-haulers in our sample is not surprising for post-viral olfactory dysfunction (54) , and in other recent datasets (i.e., healthcare workers in the UK (55) and Sweden (56) , and social media scraping (18,57) , parosmia is also emerging as a common sequela of COVID-19.…”
Section: Discussionsupporting
confidence: 59%
“…Presently, SCENTinel 1.1 accurately predicted group classification in participants who experienced olfactory disorders as a result of COVID-19, which supports the use of SCENTinel 1.1 to understand COVID-19 olfactory symptoms. It also supports the use of SCENTinel 1.1 as a tool to help detect and monitor sudden loss of smell, which is a symptom of COVID-19 (5,55), as well as parosmia, an evolving symptom of COVID-19 (31,36,37). Early diagnosis of olfactory impairment is critical for establishing successful outcomes to treatment regimes like olfactory training (56) which has recently shown effectiveness with patients with parosmia (57).…”
Section: Discussionmentioning
confidence: 68%
“…This reliance on self-report leaves estimates of qualitative olfactory disorders likely underrepresented, only diagnosed when individuals consult specialists. However, even with subjective reports, qualitative olfactory disorders are present in more than half of those reporting smell impairment (36)(37)(38), and distinct features of parosmia and phantosmia are beginning to surface (31). Parosmia encompasses distortions of a known odor, often experiencing pleasant odors as unpleasant or vice versa (39), so one way to assess parosmia directly is to have participants rate the pleasantness of two oppositely valenced odors (i.e., a pleasant and unpleasant odor).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that parosmia is caused by decreased repair of olfactory neurons in the neural circuit, so there is a possibility of the emergence of immature neurons[ 33 ]; in previous studies, parosmia showed a poor prognosis [ 9 ]. Unfortunately, in a recent study, nearly half of COVID-19 survivors complained of parosmia after one and a half years [ 5 ]. Therefore, parosmia in the context of post-viral olfactory disorders cannot be concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Anosmia—disappearance of olfactory function—could present as the only symptom of COVID-19 [ 2 , 3 ], in which the individuals presenting influenza-like symptoms are 6–10 times more likely to be COVID-19-positive [ 3 , 4 ]. However, the chance of olfactory dysfunction to persist was up to 24% in more than 7 months post-COVID-19 onsets—with 23.3% of the patients complaining of complete anosmia 35% [ 5 ], which causes slightly morbid inconvenience in 1 out of 3 individuals [ 6 ]. The inconvenience was described in many degrees, including a lower drive to cook and eat resulting in weight loss, increasing social anxiety and anxiety due to cleanliness, and one that could be potentially life-threatening: failure to detect hazards such as gas and fire, thus provoking more anxiety when alone [ 7 ].…”
Section: Introductionmentioning
confidence: 99%